Indonesian Port Cluster Simulation Game: Understanding Complex System Through Simulation Game - Armand Omar Moeis; Shara Marcheline; Arry Rahmawan Destyanto; Teuku Yuri Zagloel; Akhmad Hidayatno (Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2020)
Port Cluster is a collection of interdependent and involved companies in related activities in the same port area. Port clusters can be categorized as infrastructure. One of the characteristics of infrastructure is the number of parties involved in a problem, referred to as a Multi-Actor System. In a multi-actor system, policymaking becomes more complicated because it cannot be based on only one party's interests. Policymaking in this domain requires contemporary approaches where one of them is Simulation Gaming. This paper shows how Simulation Gaming can serve as an approach to comprehend the Indonesian Port Cluster, a multi-actor system.